International Mobility and Educational Desire Chinese Foreign Talent Students in Singapore / by Peidong Yang. - Yang, Peidong. (Anthropological Studies of Education, 2016)
This book examines the Singapore government’s controversial practice of recruiting students from China and granting them full scholarships on the condition of a service “bond”. It offers detailed ethnographic accounts of the Chinese “foreign talent” students’ educational and cross-cultural experiences in Singapore to illustrate the complex intersections between international mobility and educational desire. In doing so, the book presents contemporary Singapore society’s concerns over immigration and cross-cultural encounters from a unique perspective.